PROMOTING TEACHER NETWORK FOR TEACHER PROFESSIONAL DEVELOPMENT IN INDONESIA - Kusumawardhani, Aurora P.; Munfa’ati, Farid (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2017)
Teacher Professional Development (TPD) is very important for teachers in Indonesia for maintaining their quality of profession. Also, by conducting TPD, the teachers could improve their competences and skills for the enhancement of their teaching practice which brings the increase of students’ achievement and the quality of national education later. Various activities can be conducted by the teachers for their TPD; nevertheless, many Indonesian teachers are unwilling to do TPD effectively. In this paper, we propose teacher network to be used by Indonesian teachers. The compatible and cost-effective nature of teacher network would be advantageous for the teachers. This paper provides three ways to do of teacher learning networks along with their advantages which can be considered to assist Indonesian teachers to have an effective TPD.